KONSEP PENDIDIKAN AL-GHAZALI DAN RELEVANSINYA DALAM SISTEM PENDIDIKAN DI INDONESIA - Nurohman (AS-SALAM, 2020)
This article aim to describe the relevance of the concept of Al-Ghazali Education to the education system in Indonesia. Research methods in this article conducted with literature study on the works of Al-Ghazali. Research result This can be explained that according to Al-Ghazali the key to education is the heart because the heart is the essence of humanity which does not lie in the physical element. The concept of education that was coined by Imam Al-Ghazali is very relevant to the education system in Indonesia. This is in terms of educational goals, the concept of educators, students, learning methods, curriculum, especially character education. Which in its application puts forward the aspects of intellectual, moral, and spiritual development. Positive impact What is expected with this article is that educational institutions can adopt the concept of Al-Ghozali Education to develop the potential of students to become human beings who believe and have devotion to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become citizens. democratic and responsible.